Diagnosing cardiac amyloidosis in every-day practice: A practical guide for the cardiologist. (June 2020) - Papathanasiou, Maria; Carpinteiro, Alexander; Rischpler, Christoph; Hagenacker, Tim; Rassaf, Tienush; Luedike, Peter
Abstract: Cardiac amyloidosis (CA) has emerged as a previously underestimated cause of heart failure and mortality. Underdiagnosis resulted mainly from unawareness of the true disease prevalence and the non-specific symptoms of the disease. CA results from extracellular deposition of misfolded protein fibrils, commonly derived from transthyretin (ATTR) or immunoglobulin light chains (AL). A significant proportion of older patients with heart failure and other extracardiac manifestations suffer from ATTR-CA, whereas AL-CA is still considered a rare disease. This article provides an overview of CA with a special focus on current and emerging diagnostic modalities. Furthermore, we provide a diagnostic algorithm for the evaluation of patients with suspected CA in every-day practice.